Prototype of Integrated Health Service System for Diabetes Mellitus Prevention: Indonesian Population - Prasetyo Kusumo Mahendro; Affandi Yogi; Mei Chan Chong (BIO Web of Conferences)
The low knowledge about Diabetes Mellitus health service systems in other countries causes Indonesian migrant workers and students to choose not to be checked when they feel sick. The aims of this study to design a prototype of an integrated health service system for foreign in Taiwan. This study using Action Research method with two cycles, the first cycle was to designing prototype framework and the second cycle was to socialization of the prototype that has been developed. This study was conducted on February 2024 at Taiwan city with 85 participants. The findings of this study indicate that the integrated health service system prototype can provide assistance to Indonesian population to understand the operation of the health system, how to access the health services available in Taiwan, and help them understand their rights as patients and health insurance claims procedures. Effective socialization about the integrated healthcare system provides significant benefits, including helping to overcome barriers faced by Indonesian population in accessing healthcare services in Taiwan. It also assists them in enhancing their skills in managing their personal health and improve their quality of life by managing their health conditions more effectively and taking appropriate preventive measures.